2022
DOI: 10.1101/2022.12.28.522077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A basic model of calcium homeostasis in non-excitable cells

Abstract: The level of cytosolic calcium (Ca2+) in cells is tightly regulated to about 100 nM (pCa ≈ 7). Due to external stimuli, the basal cytosolic Ca2+ level can temporarily be raised to much higher values. The resulting Ca2+ transients take part in cell-intrinsic signals, which result in cellular responses. Because of its signaling importance and that high levels of Ca2+ can lead to apoptosis, regulation and homeostatic control of cytosolic Ca2+ is essential. Based on experimentally known molecular interactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…There is evidence that intracellular Ca stores leak Ca into the cytosol [3942]. Analyzing the data by Camello et al [41] and Luik et al [42], we observed (S4 Text and [43]) that the kinetics of the two recorded leaks were surprisingly different. While Camello et al [41] found practically zero-order kinetics with respect to ER calcium and leak rates at around 0.25 μ M/s, the data by Luik et al [42] show clean first-order kinetics with respect to ER calcium.…”
Section: Resultsmentioning
confidence: 67%
“…There is evidence that intracellular Ca stores leak Ca into the cytosol [3942]. Analyzing the data by Camello et al [41] and Luik et al [42], we observed (S4 Text and [43]) that the kinetics of the two recorded leaks were surprisingly different. While Camello et al [41] found practically zero-order kinetics with respect to ER calcium and leak rates at around 0.25 μ M/s, the data by Luik et al [42] show clean first-order kinetics with respect to ER calcium.…”
Section: Resultsmentioning
confidence: 67%
“…There is evidence that intracellular Ca stores leak Ca into the cytosol [43][44][45][46]. Analyzing the data by Camello et al [45] and Luik et al [46], we observed (S4 Text and [47]) that the kinetics of the two recorded leaks were surprisingly different. While Camello et al [45] found practically zero-order kinetics with respect to ER calcium and leak rates at around 0.25 μM/s, the data by Luik et al [46] show clean first-order kinetics with respect to ER calcium.…”
Section: Plos Onementioning
confidence: 61%
“…Additionally, AgNPs may cause apoptosis via the caspase-dependent mitochondrial pathway, which has been shown to alter cell dynamics, harm the cell membrane, inactivate ATPase activity to suppress Ca 2+ -ATPase, Na+/K+-ATPase and Ca 2+ /Mg 2+− ATP as produce excessive amounts of ROS and MDA, sensitize cell signaling to the release of cytochrome C and pro-apoptotic protein into the cytoplasm, and activate the caspase cascade as reported by 100 ; 101 . Clearance of Ca 2+ and cell homeostasis maintenance are controlled by the calmodulin (CaM)-dependent enzyme Ca 2+ -ATPase, which can prevent cells from going through apoptosis 102 .…”
Section: Discussionmentioning
confidence: 99%